PENGARUH PENGGUNAAN KOSMETIK TERHADAP ACNE VULGARIS PADA REMAJA PUTRI KELAS I DAN KELAS II SMA NEGERI 4 BANDA ACEH - Andri Andri; Mila Mauliza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Acne vulgaris is a common inflammatory condition in the polysebaceous unit that often occurs in adolescents and young adults. The exact cause of acne vulgaris is not yet known with certainty, but there are several factors that influence it such as genetic, hormonal, diet, cosmetic use, trauma, infection and psychological. The purpose of this study was to determine the effect of the use of cosmetics with acne vulgaris in adolescent girls class I and class II of SMAN 4 Banda Aceh. The study design used correlational design with cross sectional approach. The population in this study were 327 adolescents. The research sample uses simple random sampling of 180 teenagers. Data collection techniques used were approach and observation. Data analysis method used is chi-square. Research instruments using questionnaires, and physical examination (inspection). The independent variable of research is cosmetic use while the dependent variable is acne vulgaris. The results showed that the majority of students used cosmetics as many as 143 (79.4%), and as many as 37 (20.6%) students did not use cosmetics. Chi-square analysis results obtained p value = 0.017 α (0.05) which means that there is an influence between the use of cosmetics with acne vulgaris in young women Class I and Class II at SMAN 4 Banda Aceh.Keywords: Acne Vulgaris, Cosmetic Use, Teenager Girl